Высокоэффективная система очистки воздуха для военных гусеничных машин - Борисюк, М. Д.; Климов, В. Ф.; Анипко, О. Б.; Магерамов, Л. К.-А.; Колбасов, А. Н.; Кудреватых, Д. Н. (НТУ "ХПИ", 2008)
The article states the necessity of developing a reliable air cleaning system for army tracked vehicles. Presented is the data of the air cleaning system of diesel and gasturbine engines, developed are the main ways of improvement of the air cleaning systems.
Keywords: система воздухопитания; почвенно-климатические зоны; эффективные циклоны; кассеты